EFFECT OF CONSUMING RED DRAGON FRUIT (HYLOCEREUS COSTARICENSIS) JUICE ON THE LEVELS OF HEMOGLOBIN AND ERYTHROCYTE AMONG PREGNANT WOMEN - Ari Widyaningsih; Onny Setiyani; Umaroh Umaroh; Muchlis Achsan Udji Sofro; Faisal Amri (Belitung Raya Foundation, Indonesia, 2017)
Background: Iron deficiency is the most common cause of anemia during pregnancy. Red dragon fruit is assumed having much iron to increase hemoglobin and erythrocyte level. Objective: This study aims to examine the effect of dragon fruit juice on levels of hemoglobin and erythrocytes. Methods: This was a quasi-experimental research with non-equivalent control group design. There were 34 respondents recruited in this study using consecutive sampling. The samples were divided into intervention group (17 respondents) and control group (17 respondents). Data were analyzed using independent t-test and paired t-test. Results: There was a statistically significant effect of red dragon fruit juice Hb level on the 7th day of intervention with p-value 0.037 (<0.05), but there was no significant effect on hemoglobin level in the 14th day of intervention with p-value 0.140 (>0.05). This study also revealed that there was a statistically significant effect of red dragon fruit juice on pregnant women's erythrocyte level on the 7th day with p-value 0.025 (<0.05), but there was no significant effect on the erythrocyte level in the 14th day of intervention with p-value 0.094 (> 0.05). Conclusion: There was a statistically significant effect of red dragon fruit juice on hemoglobin and erythrocyte levels. This study provides the insight of knowledge that the red dragon fruit juice can be an alternative treatment to deal with anemia among pregnant women.